TINJAUAN KOREKSI FISKAL LABA RUGI KOMERSIAL PADA PT.SWAKITA INDONESIA - Yenti S, Dame Febri; Sitorus, Frangky Yosua; Lumbantoruan, Rutman L.Toruan (Buletin Ekonomi, 2017)
Fiscal correction performed by the taxpayer because there are differences in the calculation of the profit according to the accounting in particular (commercial) with the profit according to the tax (fiscal). Knowing PT.Swakita Indonesia in the income statement in accordance with the tax laws of Corporate Income Tax Act No. 36 of 2008 Article 9 paragraph 1 letter (b) that "can not be deducted in the gross income of the company are the costs incurred or charged by the company for the personal benefit of shareholders, partners or members, such as a personal home improvement, travel expenses, the cost of insurance premiums paid by the company for the benefit of private shareholders or their families ". As for the burden or expense on PT Swakita Indonesia with fiscal correction amount Rp 5,158,850,815Keywords : Taxation, Fiscal correction, Gain or loss of commercial .